Availability and Activity of Coenzyme Q10 in Selected Malaysian Freshwater Fish - Mohd Dom, Nur Sumirah (2009)
The present study was done to determine the availability of CoenzymeQ10 and to screen the antioxidant activity of the liver, intestine, muscle and egg of selected Malaysian freshwater fish extracts using DPPH assay. Besides, the study was also done to see the interactions of CoQ10 and α-tocopherol in in vitro assay. The presence of Coenzyme Q10 (CoQ10) in the muscle, liver, intestine and eggs of nine selected Malaysian Freshwater Fish consisting of Keli (Clarias batrachus), Puyu (Anabas testudineus), Tilapia Merah (Oreochromis niloticus), Tilapia Hitam (Oreochromis mossambicus), Rohu (Labeo rohita), Patin (Pangasius polyuranodon), Lampam Jawa (Puntius gonionotus), Lampam Sungai (Puntius schwanenfeldii) and Lee Koh (Cyprinus carpio) were determined using High Performance Liquid Chromatography (HPLC). The results demonstrated the presence of CoQ10 at variable amounts in different tissues and species of the Malaysian freshwater fish studied. The total amount of CoQ10 present in all the tissues were found in the order of Tilapia Hitam mossambicus) (8.251 μg/g), Tilapia Merah (Oreochromis niloticus) (6.259 μg/g), Keli (Clarias batrachus) (3.263 μg/g), Puyu (Anabas testudineus) (2.446 μg/g), Lampam Jawa (Puntius gonionotus) (1.776 μg/g), Patin (Pangasius polyuranodon) (1.436 μg/g), Rohu (Labeo rohita) (0.519 μg/g), Lee Koh (Cyprinus carpio) (0.362 μg/g) and Lampam Sungai (Puntius schwanenfeldii) (0.237 μg/g) wet weight. In this study, n-hexane/ ethanol method was used to extract the Coenzyme Q10. According to the previous study, the Bligh and Dyer method extracted mainly tocopherol, retinol and small amounts of CoQ. However, in this study, α- tocopherol was also detected in the n-hexane/ ethanol extract. Four fish species identified to have the highest amount of Coenzyme Q10 namely Tilapia Hitam (Oreochromis mossambicus) Puyu (Anabas testudineus), Tilapia Merah (Oreochromis niloticus) and Keli (Clarias batrachus) were selected for quantitation of the α-tocopherol and their antioxidant activities using 2,2- diphenyl-1-picrylhydrazil (DPPH) assay. The total body contents of α-tocopherol were found to be 12.635 μg/g, 12.631 μg/g, 7.152 μg/g and 4.482 μg/g wet weight tissues in the respective fish. From the findings, antioxidant that contributes the most to the antioxidative activity of the various tissues of fish was found to be α-tocopherol. As the fish shows low levels of Coenzyme Q10 instead of α-tocopherol and with the inability of the TBA assay to quantify the antioxidative effects in the tissues studied, further studies were carried out to assess the effectiveness of synthetic tocopherol and combination of both in vitro as a comparison to previous studies on other fish. In this study, mixtures of reduced CoQ10 and α-tocopherol standards were used. It was shown that the percentage of inhibition increased in the presence of both CoQ10 and α-tocopherol suggesting synergistic effect. Meanwhile, α-tocopherol exhibited a higher percentage with 10.99 – 60.60 % on its own compared to reduced CoQ10 with percentage inhibition ranging from 7.81 – 49.76 %. This would explain the variation of DPPH activities in the various tissues of fish and it can be concluded that α-tocopherol contributed more to the antioxidant activity compared to CoQ10 in the freshwater fish examined. In conclusion, as the Coenzyme Q10 and α-tocopherol plays vital roles in protecting human body from free radicals and retard the growth of many chronic diseases, the Malaysian freshwater fish species examined are recommended as part of the diet as both the lipophilic antioxidants are present in their tissues. The fish extracts can also be used as an alternative source of natural antioxidants to replace synthetic antioxidants in pharmaceutical aspects, as food supplement as well as in cosmetic and medical applications.